E-BOOKING SALON KECANTIKAN MENGGUNAKAN METODE UCD ( USER CENTERED DESIGN ) PADA MARIA STUDIO BEAUTY - Desi Srinarika Sitinjak; Tantri Hidayati Sinaga; Eka Rahayu (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
Development business beauty business is currently growing rapidly with following changes technology and method look somebody to style life, good women nor man always want to come on stage interesting as well as perfect for cover the drawbacks with do various method among others do maintenance beauty. Wrong business or form in field beauty which there is that is salon which is form business wich is related with service beauty, which offer various maintenance from hair ends until toe. However in beauty salon Maria Studio Beauty from consumers to owner still not maximal, then from that writer make system E-Booking beauty salon. The method used in this research is (UCD). UCD is technique that places the user at the center of the system design process. The biggest benefit of implementing UCD is that it can provide a more accurate defenition of requirements from system users. This method is used to produce a user interface design that is in accordance with the experience and needs for the user. With this Beauty Salon E-Booking system, it can make it more for consumers to choose to type of service they need and can help Maria Studio Beautu owners in managing salons using the system.